Field monitoring and numerical analysis of ground deformation induced by tunnelling beneath an existing tunnel. Issue 1 (1st January 2021) - Ahmed, Nasser Z.; El-Shourbagy, Mohamed; Akl, Adel; Metwally, Kamal
Abstract: The main challenge of implementing and constructing a new tunnel is to monitor and mitigate ground surface disturbances that may affect existing structures. This paper analyses the soil deformations induced by tunnelling under an existing tunnel and the effect of these deformations on the existing tunnel. Both field data and numerical modelling are included in this study. Numerical modelling based on the finite element method is established to simulate the tunnelling process and the technique used in the shield machine. The model is applied to the case study of the intersection between metro line 3 tunnel underneath the existing main sewage tunnel in Cairo. Settlement of the existing tunnel and the ground surface associated with the new excavation of the new metro line 3 tunnel are monitored. The numerical model is verified with the records from the field data and then used to conduct a comprehensive parametric study to investigate the effect of tunnel orientation angle, clear distance between tunnels, soil properties, and grouting around the tunnels, on ground deformation. The analysis considers the nonlinearity of the soil, the construction stages, the grouting around the tunnel, and the shield operating parameters. Findings quantify the importance of the studied parameters on the deformation and stresses of the existing tunnel and indicate that soil-grouting is the primary parameter that controls the deformations. Also, the significant effect of the studied parameters occurs within length equal from three to four times the new tunnel diameter from the intersection point.